Hubungan Aspirasi Pendidikan dengan Motivasi Belajar Mahasiswa di Fakultas Tarbiyah IAIN Kerinci - Syalmia, Yuweci; Mudjiran, Mudjiran (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
ABSTRACTThis research is motivated by the phenomenon of the number of students who consider lectures to be insignificant, leading to reduced learning motivation for students. The purpose of this study was to determine the relationship between educational aspirations and student motivation in the Tarbiyah IAIN Kerinci Faculty. This research is a descriptive correlational research with quantitative methods. The population of this study was students of Islamic Biology and Counseling Guidance at Tarbiyah Faculty of IAIN Kerinci. The total sample of 42 students was selected using the Purposive Random Sampling technique. The research instruments used were educational aspiration questionnaires and student learning motivation questionnaires. Data were analyzed by descriptive statistical techniques and Pearson Product Moment techniques with the help of the SPSS For Windows 20.0 program. The results revealed that (1) student education aspirations were in the low category (2) student learning motivation was in the moderate category, and (3) there was a positive significant relationship between educational aspirations and student learning motivation with a correlation coefficient of 0.691 at the 0,000 significance level . Based on the research findings, it is recommended that the counselor be able to provide guidance and counseling services, information services, individual counseling services, group guidance services and group counseling services to students, so as to help improve educational aspirations and learning motivation for students.